Dereplication of Mammea neurophylla metabolites to isolate original 4-phenylcoumarins. (March 2015) - Dang, Bach Tai; Guitton, Yann; Freuze, Ingrid; Grovel, Olivier; Litaudon, Marc; Richomme, Pascal; Séraphin, Denis; Derbré, Séverine
Graphical abstract: Highlights: A small database was acquired from 11 4-phenylcoumarins using LC-DAD–MS n analysis. 24 known mammea coumarins were dereplicated from Mammea neurophylla DCM extracts. The structure of 4 unreported mammea coumarins could be predicted. 2 new mammea coumarins were confirmed after purification and NMR analyses. Abstract: Mammea coumarins are isoprenylated 4-alkyl or 4-phenylcoumarins. Their distribution is limited to 3 Clusiaceae / Calophyllaceae genera. We recently reported on their presence in Mammea neurophylla bark extracts, where they exhibited anti-AGE properties associated with a prevention of the endothelial dysfunction. About 120 mammea coumarins were already described so, in order to focus further phytochemical analysis on original or bio-active compounds, we developed a methodology to facilitate the detection and identification of compounds of interest. Our aim was to develop a LC-DAD–ESI-MS n method for rapid, sensitive and simple analysis of the mammea coumarins in calophyllaceous/clusiaceous species. For that, full LC-DAD–MS n data were acquired from 11 4-phenylcoumarins previously isolated in our laboratory. Bark, leaves and fruits of M. neurophylla were then extracted with DCM using an ASE apparatus. Extracts were finally analyzed through LC-DAD–HRMS n and UV and MS profiles were compared to our database as well as literature data. Detected new compounds were isolated and their structures elucidated through 1 H, 13 C and 2D NMR analysis. Finally, 24 known mammea coumarins were dereplicated from bark, leaf and fruit DCM extracts of M. neurophylla and the structure of 4 unreported compounds could be predicted. In particular, the structures of mammea A/AA 9-hydroxyCycloF and mammea A/AB 9-hydroxyCycloF were confirmed after purification and extensive NMR analyses. By comparison of UV and mass fragmentation data from a small library of reference compounds, LC-DAD–HRMS n analysis of mammea coumarins in crude extracts allows the structure prediction of novel or bio-active compounds. This useful guiding-tool could be easily applied to other Clusiaceae / Calophyllaceae phytochemical analysis.